Understanding the causes and effects of low-risk management: implementation in projects using the DEMATEL algorithm - Lee, Chia Kuang; Wong, Wen Nee; Nurhaizan, Mohd Zainudin; Ahmad Huzaimi, Abd Jamil (Edward Elgar Publishing Ltd, 2023)
Construction projects are generally exposed to a wide range of risks, the majority of which have a direct impact on the organizations’ ability to achieve project objectives. However, many organizations overlook the importance of incorporating risk management into their projects. Previous studies paid little attention to the interdependence of the factors influencing the implementation of risk management in projects. To achieve project success and improve project performance, it is critical to identify the primary risk factors that must be carefully controlled to reduce the impact and alleviate the causes. The purpose of this study is to determine the causes and consequences of low-risk management implementation. To identify the essential causes and consequences, DEMATEL is utilized to prioritize the elements and examine their interaction. This study elicited responses from 17 people. The correlations between the causes and effects of low risk management adoption are shown to be significant. The findings also revealed that resistance to change is the most important factor for a lack of risk management adoption. Consequently, management should pay more attention to this issue in order to improve risk management and thus improve project performance in construction projects.